Pemberdayaan Masyarakat Sebagai Upaya Meningkatkan Potensi Desa Pada Era Digital Di Desa Ponowaren Sukoharjo - Hadi, Syamsul (Journal of Dedicators Community, 2024)
Ponowaren Village is one of the villages in Tawangsari District, Sukoharjo Regency, Central Java Province, which known as a developing village. It has progressed in agriculture and developed its economy through UMKM. The UNS Ponowaren Kuliah Kerja Nyata (KKN) activity aims to optimize and improve human resources in the village in order to improve the management of UMKM and the development of village administration to the fullest. This activity consists of one main program and nine supporting programs focusing on community development. The main program includes socializing the use of QRIS for UMKM actors in Ponowaren Village. Meanwhile, the supporting programs consist of updating digital content for social media in Ponowaren Village, procurement of 5M, assistance in learning Indonesian Language and Literature, poetry competitions, implementation of healthy gymnastics, quiz competitions, implementation of K3 for UMKM Furniture, manufacture of immunity-boosting drinks, and procurement of information boards at poskamling. These programs can be appropriately implemented with the support of the local government, village government, and the community's enthusiasm to contribute to the programs that have been prepared. Â